Quality of Work Life and Its Impact on Job Performance: A Study of S.B.I & HDFC Banking Professionals - Chanana, Meenakshi; Kumar Gupta, Surender (International Research Journal of Management, IT & Social Sciences, 2016)
Quality of work life is a process of work organizations, which enables its members at all levels to actively participate in shaping the organization, environment, methods and outcomes. This value-based process is aimed towards meeting the twin goals of enhanced effectiveness of organization and improved quality of life at work for employee. The paper conducted study on work life quality of workforce in the banks of district Yamuna Nagar, Haryana where the aim was to find out the different factors which influences the job performance. The result of the study shows that there is high impact of quality of work life on the performance of the employees and out of the perceptual factors of quality of reward, management support, challenging work content and career & growth opportunity are the main factor which the employees think are the important factors of quality of work life which leads them to perform well.